UP-FRONT TRIPLE COMBINATION THERAPY FOR PULMONARY ARTERIAL HYPERTENSION ASSOCIATED WITH SYSTEMIC SCLEROSIS: A CASE REPORT - A. V. Volkov; N. N. Yudkina; E. V. Nikolaeva; I. A. Kurmukov (Научно-практическая ревматология)
Pulmonary arterial hypertension (PAH) is a progressive and irreversible disease characterized by a steady increase in pulmonary vascular resistance (PVR) and death. Introduction of current PAH-specific drugs has not solved the problem of follow-up of critical patients with PAH associated with systemic sclerosis (SSc). Clinical trials have shown that 1-, 2- and 3-year survival rates are 77, 46, and 33%, respectively. Arguments in favor of starting triple PAH-specific therapy that substantially improves the prognosis of this critical group of patients are being accumulated. The paper describes Russia’s first clinical case of successful up-front triple combination therapy (iloprost, bosentan and sildenafil) in a 40 year old female with SSc and diagnosed functional class (FC) IV PAH. There were clinical, laboratory, and hemodynamic improvements already at 2 weeks after therapy initiation. Thirty-month therapy resulted in a reversal of FC from IV to II, relieved the signs of right ventricular failure, complete right ventricular reverse remodeling and subnormalization of hemodynamic parameters. Hemodynamic improvement including reductions in right atrial pressure to 4 mm Hg, mean pulmonary arterial pressure to 26 mm Hg, and PVR to 2.2 Wood units and an increase in cardiac output up to 7.4 l/min, despite preserved elevated uric acid levels (432 μmol/l). The intriguing feature of this case is critically low values of % predicted/carbon monoxide lung diffusion capacity, which rose from 17% to only 22%, in the presence of positive changes. This clinical case demonstrates the predictive capabilities of up-front triple combination therapy for severe PAH associated with SSc.